The Effect Of Adding Tofu Dregs Flour On The Quality Of Dimsum Wrappers - Viora, Martha; Andriani, Cici; Kasmita, Kasmita; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The dimsum skin is the outer layer that surrounds the dimsum filling and is often referred to as the dumpling skin which is generally made of wheat flour. The dimsum skin in this study is made from tofu pulp flour. Tofu pulp flour is used as an additive to dimsum peels because it contains a fairly high level of protein, namely in 100 grams of tofu pulp still contains 21.66% protein. The purpose of this study is to determine the effect of the addition of tofu pulp flour on the color, aroma, texture, and taste of dimsum skin. Testing the quality of the dimsum skin uses a qualitative method using an Organoleptic test through the assessment of panelists. The experiment used a Complete Randomized Design (RAL) with 3 treatments and 3 replicates. The addition of tofu pulp flour to be tested is 0%, 50% and 60%. The variables to be studied include the independent variable, namely the addition of tofu pulp flour, while the bound variable is the quality of dimsum skin, which includes the color, aroma, texture, and taste of dimsum skin. By using variant analysis (ANAVA), the results of the study were obtained which showed that there was no real effect in the addition of tofu pulp flour on the quality of color, aroma, texture, or taste in the dimsum skin.